2021
DOI: 10.1002/eap.2361
|View full text |Cite
|
Sign up to set email alerts
|

Predicting anoxia in low‐nutrient temperate lakes

Abstract: Absence of dissolved oxygen (anoxia) in the hypolimnion of lakes can eliminate habitat for sensitive species and may induce the release of sediment‐bound phosphorus. Lake anoxia generally results from decomposition of organic matter, which is exacerbated by high nutrient loads. Total phosphorus (TP) in lakes is regulated by static aspects of the lake’s watershed, but lake TP can be readily increased by human activities. In some low‐nutrient lakes, basin morphometry may induce naturally occurring anoxia. The oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
4
1
Order By: Relevance
“…Morphometric variables, however, could not predict the presence of hypoxia. This finding is in contrast with a previous study that found that morphometry successfully predicted hypoxia in low nutrient lakes (Deeds et al 2021). In our study, morphometry emerged in predicting hypoxic hypolimnia in the regression tree as the secondary variable and in the random forest focused on dystrophic lakes.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Morphometric variables, however, could not predict the presence of hypoxia. This finding is in contrast with a previous study that found that morphometry successfully predicted hypoxia in low nutrient lakes (Deeds et al 2021). In our study, morphometry emerged in predicting hypoxic hypolimnia in the regression tree as the secondary variable and in the random forest focused on dystrophic lakes.…”
Section: Discussioncontrasting
confidence: 99%
“…The influence of heavy precipitation on sudden allochthonous DOC inputs has been shown to cause and maintain hypoxic conditions in a shallow lake (Brothers et al 2014), but the role of browning in driving lakes to hypoxia and anoxia remains under explored. Some studies found no relationships specifically with DOC (Nürnberg 1995; Deeds et al 2021; Senar et al 2021), whereas another site‐specific study did, but only in oligotrophic lakes (Knoll et al 2018). This could potentially be due to a differential influence of browning depending on the nutrient‐color status of the lake.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Poorer performance for lake morphometry variables was expected, as the model is trained to minimize pixel-wise error. While modeling of lake-level morphometric variables is sufficient for some applications, others require bathymetric maps, for example, for analyses of the distribution and biomass of submerged macrophytes (Duarte and Kalff 1986;Lehmann 1998), greenhouse gas emissions (Li et al 2020), and extent of anoxia (Deeds et al 2021). For such applications, having bathymetric maps available enables improved quantification of such processes on regional to global scales.…”
Section: Lake Bathymetric Mapsmentioning
confidence: 99%
“…Morphometric variables such as lake volume, mean ( z mean ), and maximum ( z max ) depths are important predictors of many processes, including water retention time, nutrient loading, and cycling, as well as productivity of phytoplankton, zooplankton, and fish (Håkanson 2005). Even more usefully, hypsographic relationships and bathymetric maps communicate the extent of littoral zones colonized by submerged plants (Seekell et al 2021) and hypolimnion zones that might be subject to seasonal oxygen depletion (Deeds et al 2021), and also can be incorporated into physical models (Fricker and Nepf 2000). Lake bathymetry and derived morphometric variables are thus used extensively to investigate lake functioning.…”
mentioning
confidence: 99%